Assessment for learning in the EYFS - Sargent, Marianne (London Featherstone Education, 2011)
"The 'Key Issues' series addresses some of the major challenges facing Early Years settings and Primary schools. This exciting new title comes under the 'Every Child Matters' remit and explains in a practical way, what assessment for learning entails and how it can be successfully implemented in the EYFS" -- Provided by publisher.
Includes bibliographical references (pages 62-64).
Keywords: Educational tests and measurements -- England; Early childhood education -- England -- Evaluation